Fenomen audycji omawiających listy do redakcji (tzw. skrzynki) w Polskim Radiu okresu międzywojnia = The phenomenon of broadcasts discussing letters to the editor (the so-called "mailbag") on Polish Radio during the interwar period - Zwolińska-Pieniążek, Paulina (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The relationship between a broadcaster and a recipient, which is both contrasting and coherent, is the foundation of the mass media existence, therefore from the beginning of the Polish radio broadcasting, great emphasis was placed on building a strong and lasting bond between radio broadcasters and recipients. The article presents radio "boxes" - special programs emitted by Polish Radio, in which letters sent to the editorial office by listeners were read and answered on the air.
Keywords: "skrzynki" radiowe; "Skrzynka Ogólna"; "Skrzynka Odpowiedzi"; "Francuska Skrzynka Katowic"; radio; audycja radiowa; polskie radio; nadawca; odbiorca; relacje nadawczo-odbiorcze; radio "boxes"; "General Box"; "Response Box"; "French Box of Katowice"; radio broadcast; Polish radio; sender; recipient; transmitter-receiver relations